2006
DOI: 10.1002/syn.20250
|View full text |Cite
|
Sign up to set email alerts
|

Expression of excitatory amino acid transporter interacting protein transcripts in the thalamus in schizophrenia

Abstract: The excitatory amino acid transporters (EAATs) are a family of plasma membrane proteins that maintain synaptic glutamate concentration by removing glutamate from the synaptic cleft. EAATs are expressed by glia (EAAT1 and EAAT2) and neurons (EAAT3 and EAAT4) throughout the brain. Glutamate reuptake is regulated, in part, by EAAT-interacting proteins that modulate subcellular localization and glutamate transport activity of the EAATs. Several lines of investigation support the hypothesis of glutamatergic abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 49 publications
2
32
1
Order By: Relevance
“…The authors of one of the studies attributed this effect to the difference in the ages of the subjects included in the two studies (Eastwood and Harrison, 2005;Uezato et al, 2009). These findings, as well as the conclusions of the BrainCloud project, are consistent with reports of gene expression-specific associations with age of death (Eastwood and Harrison, 2005;Huerta et al, 2006;McCullumsmith et al, 2007;. Agerelated changes are likely not limited to transcripts.…”
Section: Age At Deathsupporting
confidence: 89%
“…The authors of one of the studies attributed this effect to the difference in the ages of the subjects included in the two studies (Eastwood and Harrison, 2005;Uezato et al, 2009). These findings, as well as the conclusions of the BrainCloud project, are consistent with reports of gene expression-specific associations with age of death (Eastwood and Harrison, 2005;Huerta et al, 2006;McCullumsmith et al, 2007;. Agerelated changes are likely not limited to transcripts.…”
Section: Age At Deathsupporting
confidence: 89%
“…Increased VGLUT1 mRNA could also be secondary to decreased cortical inhibitory tone, or a reaction to abnormal subcortical input to the ACC. Several studies have demonstrated abnormalities in GABAergic interneurons in the PFC, while others have found changes in regions with dense reciprocal innervation from the PFC, such as the thalamus [24,31,[43][44][45][46][47]. For example, transcript expression for VGLUT2 and glutaminase was increased in the dorsal thalamus in schizophrenia in a study using a different sample from the same brain bank we used in this study [24,46].…”
Section: Discussionmentioning
confidence: 96%
“…Some of the sensory and cognitive disturbances seen in schizophrenia are consistent with glutamatergic dysfunction of thalamic circuitry. Transcript expression studies of glutamatergic molecules in the thalamus by our laboratory have revealed many changes in this illness, including increased vesicular glutamate transporters, decreased NMDA receptor subunits and proteins involved in receptor trafficking, increased astrocytic EAATs 1 and 2, and increased EAAT interacting proteins (Clinton et al, 2006, Clinton and Meador-Woodruff, 2004, Huerta et al, 2006, Ibrahim et al, 2000, Smith et al, 2001a, Smith et al, 2001b. We have also demonstrated that glutamine synthetase transcript levels in the thalamus are increased in several nuclei, including those that project to the ACC and STG (Bruneau et al, 2005).…”
Section: Expression Of Glutamine Synthetase In Schizophreniamentioning
confidence: 99%